INDEPENDENSI KEWENANGAN KOMISI PEMBERANTASAN KORUPSI PASCA PERUBAHAN UNDANG-UNDANG KOMISI PEMBERANTASAN KORUPSI - Muhammad Habibi (Cepalo, 2020)
After the enactment of Law Number 19 of 2019 concerning the Second Amendment to Corruption Eradication Commission (KPK) Law, the position of the KPK which was originally a non-governmental institution is now included in the branch of governmental power branches (Auxiliary State Organs). All corruption eradication institutions (outside the police and prosecutors) that still survive are only the Corruption Eradication Commission, namely an independent commission which has been given pro justitia authority in carrying out acts of corruption so far not without criticism. In carrying out their duties and functions (before the revision of the Act), experts criticized many of the institutions that were "independent". The purpose of writing this journal is to find out whether the amendment of Corruption Eradication Commission Law has given birth to the concept of an independent state institution for the KPK. This study uses a normative legal research method, meanwhile, the approach taken uses a statutory approach and a conceptual approach. The results of this study explain if the overall amendment to the KPK Law has not yet given birth to the concept of an independent state institution because there are still provisions in the article to intervene in the independence of the KPK's authority for corruption.